Dam Engineering Recent Advances in Design and Analysis - Fu, Zhongzhi; Bauer, Erich (IntechOpen, 2021)
Dams are critical structures in the sense that damage or breach of even a small dam may cause an unacceptable loss of life and property. Therefore, the safety of dams over the intended lifespan is of utmost importance for unrestricted operation. The basic prerequisites for any safe and successful operation of a dam include state-of-the-art design, experimental investigations of the construction material and properties of the foundation, a refined theoretical analysis of relevant load cases, and high-quality construction. In the past decades, many advancements have been achieved in both construction technologies and design, including those for the prediction of the long-term behavior of dams under various loading conditions. As such, this book examines these advancements with respect to the design, construction, and performance of earth, rockfill, and concrete dams. Over eight chapters, this book provides a comprehensive overview of the latest progress and research in dam engineering.